2021
DOI: 10.1038/s41524-021-00547-z
|View full text |Cite
|
Sign up to set email alerts
|

Diverse electronic and magnetic properties of CrS2 enabling strain-controlled 2D lateral heterostructure spintronic devices

Abstract: Lateral heterostructures of two-dimensional (2D) materials, integrating different phases or materials into a single piece of nanosheet, have attracted intensive research interests for electronic devices. Extending the 2D lateral heterostructures to spintronics demands more diverse electromagnetic properties of 2D materials. In this paper, using density functional theory calculations, we survey all IV, V, and VI group transition metal dichalcogenides (TMDs) and discover that CrS2 has the most diverse electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 71 publications
0
35
0
Order By: Relevance
“…Since the topological properties of QAH materials can be identified with Chern numbers, 18 they are also called Chern insulators. [19][20][21][22][23][24] Meanwhile, magnetic 2D materials, including 2D half metals (HMs), [25][26][27][28][29][30][31] 2D half semiconductors (HSs), 29,[32][33][34][35][36] 2D half-valley materials, [37][38][39][40] etc., were also employed in the fields of condensed matter physics and materials science due to their promising nanoscale spintronic applications. 100% spin-polarized electronic current can be generated and detected in HMs and HSs, which are deemed to be ideal materials for the fabrication of spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Since the topological properties of QAH materials can be identified with Chern numbers, 18 they are also called Chern insulators. [19][20][21][22][23][24] Meanwhile, magnetic 2D materials, including 2D half metals (HMs), [25][26][27][28][29][30][31] 2D half semiconductors (HSs), 29,[32][33][34][35][36] 2D half-valley materials, [37][38][39][40] etc., were also employed in the fields of condensed matter physics and materials science due to their promising nanoscale spintronic applications. 100% spin-polarized electronic current can be generated and detected in HMs and HSs, which are deemed to be ideal materials for the fabrication of spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…As a representative of 2D TMDs, the chromium disulfide (CrS 2 ) monolayer was synthesized via the chemical vapor deposition (CVD) method in 2019 [ 21 ]. Interestingly, due to its unique properties, the CrS 2 monolayer has wide applications in spintronic devices [ 36 , 37 ]. For example, Chen et al suggested that CrS 2 has the most diverse electronic and magnetic properties: antiferromagnetic (AFM) metallic, non-magnetic (NM) semiconductor, and ferromagnetic (FM) semiconductor with a Curie temperature of ~1000 K [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, due to its unique properties, the CrS 2 monolayer has wide applications in spintronic devices [ 36 , 37 ]. For example, Chen et al suggested that CrS 2 has the most diverse electronic and magnetic properties: antiferromagnetic (AFM) metallic, non-magnetic (NM) semiconductor, and ferromagnetic (FM) semiconductor with a Curie temperature of ~1000 K [ 36 ]. Moreover, Zhang et al reported that the magnetic properties of CrC 2 monolayer can be effectively tuned by doping metal atoms [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In addition, ferromagnetic transition metal dichalcogenides (TMDs), as a new type magnetic semiconductor monolayer, have been employed to construct heterostructures such as CrTe 2 |Gr( n ML)|CrTe 2 , 13 VTe 2 |Gr|VTe 2 , 14 1T-MoSe 2 |1T-VSe 2 |2H-WSe 2 |1T-VSe 2 |1T-MoSe 2 , 15 1T-MoS 2 |1T-VSe 2 |1H-MoS 2 |1T-VSe 2 |1T-MoS 2 16 and 1T′-CrS 2 |1T-CrS 2 /2H-CrS 2 |1T′-CrS 2 . 17 By increasing the thickness of the Gr barrier layers in 1T-CrTe 2 based MTJ, Zhou et al also noticed a tunable TMR effect. 13 Recently, Yang et al built a 2D ferromagnetic semiconductor CrPS 4 tunnel barrier with a large thickness range, and they predicted that the TMRs generally increase from 140% (3 layers) to a surprising 3.7 × 10 6 % (10 layers).…”
Section: Introductionmentioning
confidence: 99%